2012
DOI: 10.1029/2012gl051022
|View full text |Cite
|
Sign up to set email alerts
|

On the reported ionospheric precursor of the 1999 Hector Mine, California earthquake

Abstract: Using Global Positioning System (GPS) data from sites near the 16 Oct. 1999 Hector Mine, California earthquake, Pulinets et al. (2007) identified anomalous changes in the ionospheric total electron content (TEC) starting one week prior to the earthquake. Pulinets (2007) suggested that precursory phenomena of this type could be useful for predicting earthquakes. On the other hand, and in a separate analysis, Afraimovich et al. (2004) concluded that TEC variations near the epicenter were controlled by solar and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
64
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 28 publications
3
64
0
Order By: Relevance
“…They show that the TEC changes documented by Pulinets et al (2007) are not anomalous but normal variations on global scale, and, therefore, these changes are not related to the localised seismic activity of the Hector Mine area. This paper confirms the results of Afraimovich et al (2004) and Thomas et al (2012). Through the use of geomagnetic indices time series it is shown that the presumed precursor of Pulinets et al (2007) was a normal TEC variation induced by solar-terrestrial interaction.…”
supporting
confidence: 74%
See 2 more Smart Citations
“…They show that the TEC changes documented by Pulinets et al (2007) are not anomalous but normal variations on global scale, and, therefore, these changes are not related to the localised seismic activity of the Hector Mine area. This paper confirms the results of Afraimovich et al (2004) and Thomas et al (2012). Through the use of geomagnetic indices time series it is shown that the presumed precursor of Pulinets et al (2007) was a normal TEC variation induced by solar-terrestrial interaction.…”
supporting
confidence: 74%
“…In a previous paper, Afraimovich et al (2004) excluded that TEC variations, which occurred before the Hector Mine earthquake, were induced by the preparation process of the seismic event. Thomas et al (2012) reach similar conclusions by performing new analyses of the same TEC data which were investigated by Pulinets et al (2007). They show that the TEC changes documented by Pulinets et al (2007) are not anomalous but normal variations on global scale, and, therefore, these changes are not related to the localised seismic activity of the Hector Mine area.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…The authors document seismogenic changes in the multi-fractal parameters of the geomagnetic field H component starting about one month before the earthquake. As Thomas et al (2012) emphasize, these kinds of reports have motivated many researchers to study in depth the possible occurrence of earthquake precursors as well as to develop physical models to explain their generation. Thus, the results of these publications must be carefully checked.…”
Section: Discussionmentioning
confidence: 99%
“…However, since previous studies do not show strong evidence of correlation between the presumed magnetic precursors and seismic events, many scientists do not agree that these signals are really related to the earthquake occurrence. As a consequence, these researchers seriously put into question previous observations of magnetic ULF earthquake precursors and have published their findings (see Campbell, 2009;Masci, 2010Masci, , 2011aMasci, , b, 2012aThomas et al, 2009a, b) giving rise to an intense re-examination process of controversial scientific claims (see also Fraser-Smith et al, 2011;Masci, 2012d;Thomas et al, 2012).…”
Section: Introductionmentioning
confidence: 99%